The Alzheimer's Disease Sequencing Project – Follow Up Study (ADSP‐FUS): Increasing ethnic diversity in Alzheimer's genetics research with the addition of potential new cohorts. (December 2021) - Mena, Pedro Ramon; Kunkle, Brian W.; Faber, Kelley M.; Adams, Larry D.; Inciute, Jovita D.; Whitehead, Patrice L.; Foroud, Tatiana M.; Reyes‐Dumeyer, Dolly; Kuzma, Amanda B; Naj, Adam C; Martin, Eden R; Dalgard, Clifton L.; et al.
Abstract: Background: The ADSP‐FUS is a National Institute on Aging (NIA) initiative focused on identifying genetic risk and protective variants for late‐onset Alzheimer Disease (LOAD). A concern in AD genetic studies is a lack of racial‐ethnic diversity. The ADSP‐FUS collects and sequences existing ethnically diverse and unique cohorts with clinical data to expand the utility of new discoveries for individuals from all populations. Additional multi‐ethnic cohorts are presently being recruited (e.g., Amerindian, Asian and Indian). Method: The cohorts consist of participants from studies of AD, dementia, and aging‐related conditions. Clinical classification (i.e., AD, dementia, and non‐affected) is implemented using algorithms based on a minimal set of criteria derived from standard measures (e.g., global cognitive screeners, dementia rating scales, etc.) and clinical history. Data dictionaries are curated for each cohort by the FUS clinical staff. In total, the ADSP‐FUS intends to sequence over 60, 000 individuals. Biospecimens are processed and DNA is prepared and allocated through the National Centralized Repository for Alzheimer's (NCRAD). The DNA is delivered to the Uniformed Services University of the Health Sciences (USUHS) for whole genome sequencing (WGS). The resulting raw sequence data is conveyed to the Genome Center for Alzheimer's Disease (GCAD) for processing and harmonization followed QC analysis at University of Pennsylvania and University of Miami resulting in analysis‐ready genotype data. Lastly, all clinical, genotype and sequence data are sent to the NIA Genetics of Alzheimer Disease Data Storage Site (NIAGADS), serving as the ASDP‐FUS data storage, management and sharing center. Results: Over 60, 000 samples have been ascertained and are distributed by ancestry as follows: 7, 686 African; 9, 652 Hispanic; 40, 575 non‐Hispanic white (1, 400 EOAD and 3, 745 autopsy); 89 Amerindian; 4, 003 Asian and 2, 000 Indian. To date, we have sequenced 8, 208 NHW; 5, 528 African; 6, 149 Hispanic & 89 Amerindian. Conclusion: The ADSP‐FUS will enhance ongoing efforts to identify shared and novel genetic risk factors for LOAD among different populations. This project will expand our knowledge of potential genetic risk and protective variants for LOAD across all populations with the hope of developing new treatments that work for everyone.